Tinospora cordifolia GCMS profiling and cytotoxic effect on HCT 116- in vitro assay: Anticancer phytochemical screening - Manimozhi, S; Sumathi, V (Plant Science Today, 2026)
An assessment of ethylacetate extract of Tinospora cordifolia extract (TCE) antibacterial, antioxidant and cytotoxicity on HCT116 properties were undertaken in light of its possible application as an anticancer agent against colon cancer. Compounds from the stem were Soxhlet extracted with ethyl acetate and identified through GCMS. Antibacterial activity by disc diffusion and conventional in vitro antioxidant assays was performed. The cytotoxicity of the extract was studied by MTT assay. The data of the GC–MS profile highlights 20 diverse chemical compounds. The extract exhibited broad-spectrum antibacterial activity on clinical pathogens with relative inhibition of 83 to 107 % and the zone of inhibition was found to be concentration-dependent. The antioxidant assay of the extract showed the strongest DPPH scavenging with an IC₅₀ value of 12.07 µg/mL, which, although higher, showed promising free radical scavenging and the IC50 values were 331.97, 12.078 and 67.867 µg/mL on OH scavenging, DPPH and metal chelation. The effect of the extract on the viability of HCT116 colorectal carcinoma cells showed induced cell death significantly at higher concentration and the calculated IC₅₀ value was 359 µg/mL. Morphological examination and apoptosis assays further confirmed that cell death was predominantly apoptotic nature in cancerous cells. The molecular docking of compounds 2-Fluoro-3-trifluoromethylbenzoic acid from the extract was found to be strongest binding affinity and non-toxic drug likeness, identified as a promising new anticancer compound.